Gestão de pessoas e paradoxos organizacionais: contradições entre o discurso e a prática - Aguiar, José Eduardo de (2006)
The acceleration of the processes became a critical factor for companies, causing a revision of the concept of people management and the adoption of a speech that provides to the worker a perspective of bigger control over their own activity, on behalf of the necessary organizational flexibility. However, the fast implementation of new models of people management, directed towards learning and change, has caused a certain lack of synchronizing between the adoption of the new formal speech of people management and its effective implementation, provoking the occurrence of the organizational paradox known as contradictions between the speech and the practical. This research studied the work environment in six bank agencies of attendance to the customer of a financial institution, in order to identify the existing contradictions between the speech and the practical organizational. This analysis was made through the definition and analysis of the existing relationship among the theoretical foundations linked to the organizational change, people's administration, satisfaction in the accomplishment of the work, and the administration of careers, with the general objective of determining if possible contradictions within this relationship affect the worker, in his/her satisfaction to the accomplishment of the work and administration of his/her professional career. Starting from the assumption that the fast adaptation of the administrative theories provoke a series of side effects, within a context of implementation of organizational changes, it is characterized what comes to be organizational paradox, making possible the establishment of a correlation between the organizational conflicts and the worker's cognition, with this last one influencing the satisfaction in the accomplishment of the work and the administration of the professional career. Of applied nature, adopting the phenomenology and the qualitative approach to build up a case study, this work is fundamented in the bibliographical research, in the participant observation and in the data collected through documents and interviews. The characteristics of the observed phenomenon are presented of a descriptive form and the collected data analyzed inductively. The results translate the reality of the Corpus of research, materialized inside of a delimited working environment, from where has been registered different forms of the employee to perceive the existing contradictions between the organization speech and of the effective managerial practice, including the failure to perceive these contradictions, with consequences that go from indifference to revolt, from the lack of the commitment to determination of leaving the company.